ADAPTIVE PRODUCTIVITY MODEL: INTEGRATING LEAN OFFICE AND INDUSTRY 4.0 IN MODERN ADMINISTRATIVE SYSTEMS - Umami, Anjeli Riza; Jumali, Muhamad Abdul; Rusdiyantoro, Rusdiyantoro (J@ti Undip: Jurnal Teknik Industri, 2025)
In the wake of digital disruption and operational volatility, organizations are compelled to reimagine productivity beyond traditional efficiency. This study introduces an adaptive productivity model by fusing Lean Office practices with Industry 4.0 technologies—specifically IoT, AI, and Big Data analytics—within administrative systems of professional service firms. Using a mixed-methods design, data from 44 participants in a public valuation office were analyzed through multiple regression, revealing a strong predictive capacity (R² = 0.908). Lean Office (β = 0.281, p = 0.016) and Industry 4.0 (β = 0.253, p = 0.020) both demonstrated significant contributions to enhanced productivity and operational responsiveness. Over 93% of respondents observed reduced process time, while 98% acknowledged improved cross-functional collaboration. These results confirm that digital-lean convergence fosters an agile, sustainable, and data-informed working culture. The proposed model offers a future-ready framework for administrative transformation—one that is lean by design, smart by technology, and resilient by culture.